Comparative Efficacy of Hypertension Management Strategies - Schneider, Jordan; Alvarez-Betancourt, Alejandro; Elbaz, Joshua; Wenn, Peter; Makaryus, Amgad N.; Zeltser, Roman (International Journal of Angiology, 2024)
Hypertension (HTN) is a major cardiovascular risk factor and a significant contributor to disease burden in the United States. Despite therapeutic advances, gaps remain between clinical trials and practice. This study aims to bridge those gaps by evaluating antihypertensive strategies. This was a retrospective analysis of HTN patients seen at a hospital clinic from 2016 to 2022 with 3- and 12-month follow-up appointments. Demographics, history, blood pressure (BP), and medication regimen were recorded. Treatment strategies were categorized as follows: adding medication (AM), increasing dosage (ID), switching medications (SM), dropped medications (DrM), or no change (NC). Changes in systolic blood pressure (SBP) were compared using linear regressions to assess the efficacy of HTN management. Of 873 patient charts reviewed, 332 patients were included. The AM group had an adjusted ∆SBP of −11 mm Hg at 3 months (p < 0.001) and −9 mm Hg at 12 months (p = 0.006). The ID group had an ∆SBP of −8.5 mm Hg at 3 months (p = 0.074) and −7 mm Hg at 12 months (p = 0.3). ∆SBP between the AM and ID groups was not statistically significant (p = 0.8). SM was associated with an ∆SBP of −3 mm Hg at 3 months (p = 0.6) and −3 mm Hg at 12 months (p = 0.7). There are meaningful differences in SBP reduction between antihypertensive medication adjustment strategies. AM had the greatest effect on lowering SBP, with ID having a slightly lesser effect. The difference in ∆SBP between the AM versus ID groups was not significant. While further study with a larger dataset is warranted, our findings highlight trends in the efficacy of HTN management strategies to help guide therapeutic regimens.
Keywords: hypertension; antihypertensive; strategy; treatment; blood pressure; management; retrospective